2021
DOI: 10.1080/20008198.2021.1929024
|View full text |Cite
|
Sign up to set email alerts
|

Response of young patients with probable ICD-11 complex PTSD to treatment with developmentally adapted cognitive processing therapy

Abstract: Background: ICD-11 features Complex Posttraumatic Stress Disorder (CPTSD) as a new diagnosis. To date, very few studies have investigated CPTSD in young patients, and there is a need for evidence on effective treatment. Objective: The present study evaluates the applicability of developmentally adapted cognitive processing therapy (D-CPT) for CPTSD in young patients in a secondary analysis of the treatment condition of a randomized controlled trial (RCT) investigating the efficacy of D-CPT. Methods: The D-CPT … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…A typical approach is to select items based on face validity using questions that are closely representative of the suggested DSO symptoms (see Cloitre et al, 2013 for a description). Using this strategy studies have shown that interpersonal trauma as well as multiple victimization predicts CPTSD (Eilers et al, 2021 ; Sachser et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A typical approach is to select items based on face validity using questions that are closely representative of the suggested DSO symptoms (see Cloitre et al, 2013 for a description). Using this strategy studies have shown that interpersonal trauma as well as multiple victimization predicts CPTSD (Eilers et al, 2021 ; Sachser et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Four studies have to date examined treatments effects for CPTSD in youth using proxy instruments. Eilers et al ( 2021 ) examined the use of a developmentally adapted youth model of Cognitive Processing Therapy (D-CPT) for CPTSD and found that both the CPTSD and the non-CPTSD groups showed significant symptom reductions. The CPTSD group reported however higher symptom severity both before and after treatment (Eilers et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies have found CPTSD to be more prevalent than PTSD in general populations (Cloitre et al, 2019 ; Hyland et al, 2021 ) and in veteran samples (Armour, Robinson, et al, 2021 ; Mur-Crepulja et al, 2020 ; Murphy et al, 2020 ; Zerach et al, 2019 ). Trauma-focused interventions have shown efficacy in reducing CPTSD distress and symptomology (Hébert & Amédée, 2020 ; Voorendonk, De Jongh, Rozendaal, & Van Minnen, 2020 ), including several specialised variants of cognitive behavioural therapy (CBT) (Eilers et al, 2021 ; Karatzias et al, 2019 ), a personalised approach utilising multiple practices to suit the individual is recommended (Cloitre, 2021 ). In veteran treatment-seeking populations, several phase-based interventions have shown positive results (Landes, Garovoy, & Burkman, 2013 ), though it has been noted that CPTSD symptomology may act as an additional barrier to help-seeking (Williamson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bei Jugendlichen und jungen Erwachsenen wurde in einer Sekundäranalyse die entwicklungsangepasste Kognitive Verhaltenstherapie (E-KVT; Matulis, Resick, Rosner & Steil, 2014) für kPTBS untersucht (Eilers, Rimane, Vogel, Renneberg, Steil & Rosner, 2021). Die E-KVT adressiert neben der PTSS in weiteren Phasen auch SSO-Symptombereiche (Emotionsregulation, Beziehungsgestaltung).…”
Section: Behandlung Der Kptbsunclassified